Efektivitas Aplikasi CoachKu Berbasis Android terhadap Peningkatan Performa Fisik Seleksi Sekolah Kedinasan - Muhammad Ariansyah; Rahma Dewi; Nurkadri Nurkadri; Indra Kasih; Ardi Nusri (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
The selection process for Indonesian civil service schools demands high physical performance standards, yet structured and digitized physical coaching systems remain scarce. This study aimed to develop and examine the effectiveness of CoachKu, an Android-based application serving as a coach marketing platform and training support system for selection preparation. Adopting the Borg and Gall Research and Development model, the study involved 40 senior high school students as prospective selection candidates using a one-group pretest-posttest design. Instruments comprised student response questionnaires, physical performance pretests and posttests, and expert validity scales. Analytical techniques included paired sample t-test, normalized gain score (N-Gain), effect size (Cohen’s d), product-moment validity, and Cronbach’s Alpha reliability. Results revealed significant improvement between pre-test (M = 56.52; SD = 3.71) and posttest (M = 73.03; SD = 3.91) with t = 54.64, p < 0.001. The average N-Gain was 0.4024 (moderate category) and the effect size Cohen’s d = 4.25 (large category). All questionnaire items were valid (r > 0.312) with high reliability (α = 0.8745). Expert validation indicated product feasibility of 93.00% (very feasible). It is concluded that the CoachKu application is both practically and significantly effective in improving the physical performance of prospective civil service school selection candidates.